2014
DOI: 10.3390/molecules191016024
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidized Vegetable Oils Plasticized Poly(lactic acid) Biocomposites: Mechanical, Thermal and Morphology Properties

Abstract: Plasticized poly(lactic acid) PLA with epoxidized vegetable oils (EVO) were prepared using a melt blending method to improve the ductility of PLA. The plasticization of the PLA with EVO lowers the Tg as well as cold-crystallization temperature. The tensile properties demonstrated that the addition of EVO to PLA led to an increase of elongation at break, but a decrease of tensile modulus. Plasticized PLA showed improvement in the elongation at break by 2058% and 4060% with the addition of 5 wt % epoxidized palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
176
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(207 citation statements)
references
References 24 publications
25
176
0
6
Order By: Relevance
“…This interaction allows load transfer between PLA matrix and dispersed HSF particles and this leads to improved ductile properties such as elongation at break. PLA can be plasticized with relatively low amounts of epoxidized vegetable oils as reported by other authors and PLA is not absolutely miscible with epoxidized vegetable oils [23,24,44,47]. This lack of complete miscibility is evidenced by observation of fractured surfaces.…”
mentioning
confidence: 52%
“…This interaction allows load transfer between PLA matrix and dispersed HSF particles and this leads to improved ductile properties such as elongation at break. PLA can be plasticized with relatively low amounts of epoxidized vegetable oils as reported by other authors and PLA is not absolutely miscible with epoxidized vegetable oils [23,24,44,47]. This lack of complete miscibility is evidenced by observation of fractured surfaces.…”
mentioning
confidence: 52%
“…Hence, as ratio of EPO increased, the yields stress decreased as reported by Chieng et. al [11]. Meanwhile, at EPO content of 30 wt%, the yield stress decreased to 4.3 MPa and elongation-atbreak of 6%.…”
Section: Tensile Properties Of Pla/epo Blendsmentioning
confidence: 94%
“…Palm oil for example is a favourable vegetable oil because it is cheap, low in toxicity and easily available as a sustainable agricultural resource. The effect of epoxidized palm oil (EPO) on PLA/PCL was studied by [7]. They reported that EPO reduced the tensile strength and modulus of PLA/PCL blend produced via solution casting.…”
Section: Introductionmentioning
confidence: 99%